Digital Viau : histoire et aléas d’un projet en humanités numériques - Léa Saint-Raymond (Les Cahiers de Framespa)
This article aims to retrace the development of a research project, Digital Viau, which combines digital humanities and art history, in order to present, in the form of a digital library deployed with Omeka, the collection of paintings, graphic arts and sculptures constituted by George Viau in the first half of the 20th century. It lays stress on the immense part due to chance and trial and error, the errors and dead ends inherent to such a collective work, and the conflicts of interpretation that emerged between the different actors.